ANALYSIS OF THE SUSTAINABILITY OF MAIN COMMODITIES OF NUTMEG IN SOUTH ACEH REGENCY (CASE STUDY OF SAMA DUA DISTRICT) - Maisarah; Aswin Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Nutmeg, which is native to Indonesia, is also a superior plantation crop in South Aceh District. As a superior crop that concerns the lives of many farmers, the sustainability of the nutmeg crop needs attention. Sustainability research conducted in Samadua District was conducted to determine the condition of the sustainability of nutmeg plants based on the economic, social, environmental and post-harvest cultivation dimensions. The results showed that in multi-dimensional, social, and environmental dimensions, the nutmeg plant was in a fairly sustainable condition. But the nutmeg crop is less sustainable in the economic dimension, post-harvest cultivation. Therefore, the development of nutmeg in South Aceh District, especially in Samadua District, needs to consider this condition of sustainability status.